Determinação dos valores de dimensão fractal e lacunaridade de imagens microscópicas de terminações nervosas livres em ligamentos de joelho e cotovelo - Chagas Junior, José Iran Oliveira das (2024)
Fractal dimension (DF) is a mathematical area that studies objects that present repeated patterns at various scales, known as fractals. Lacunarity (LAC) allows identifying the quantity, complexity, and spatial organization of a particle and helps to characterize its organization and density. This research aims to evaluate the organization of images of free nerve endings in knee and elbow ligaments through the fractal dimension and lacunarity. This is a descriptive study, developed at the Federal University of Ceará, where digital images of histological sections by immunofluorescence were analyzed, from cadaveric knee and elbow pieces collected in a previous study by ALENCAR NETO, 2022; LIMA, 2019; COSTA, 2024. The study met the standards of resolution 466/2012 of the National Health Council. The sample was composed of 3 groups: A - meniscotibial ligament of the knee (LMT), B - anterolateral ligament of the knee (ALL), and C - lateral collateral ligament of the elbow (LCL). Among the three groups studied, groups A (LMT) and C (LCL) had the largest fractal dimension, which suggests a higher level of disorganization, the opposite of what was found in group B, which had a smaller fractal dimension, suggesting a higher level of organization. In LAC, among the groups studied, group B (LAL) had a larger lacunarity, which suggests a lower density. The analysis of the correlation of DF with LAC showed that group A (LMT) presented a moderate positive correlation; group B (LAL) presented a moderate negative correlation, and group C (LCL) a weak positive correlation. Advances in technologies, such as advanced microscopy and imaging techniques associated with fractal analysis and lacunarity, are expanding our understanding of nerve endings. These tools have potential for applications in clinical neuroscience and nerve regeneration, offering the possibility of innovative treatments and approaches. However, there is a lack of studies that employ this technique, which is what motivated this work.